Bromeliad Catchments as Habitats for Methanogenesis in Tropical Rainforest Canopies - Goffredi, Shana K.; Jang, Gene; Woodside, Walter T.; Ussler, William (Frontiers in Microbiology, 2011)
Tropical epiphytic plants within the family Bromeliaceae are unusual in that they possess foliage capable of retaining water and impounded material. This creates an acidic (pH 3.5-6.5) and anaerobic (< 1 ppm O2) environment suspended in the canopy. Results from a Costa Rican rainforest show that most bromeliads (n = 75/86) greater than 20 cm in plant height or 4-5 cm tank depth, showed presence of methanogens within the lower anoxic horizon of the tank. Archaea were dominated by methanogens (77-90% of recovered ribotypes) and community structure, although variable, was generally comprised of a single type, closely related to either hydrogenotrophic Methanoregula or Methanocella, a specific clade of aceticlastic Methanosaeta, or Methanosarcina. Juvenile bromeliads, or those species, such as Guzmania, with shallow tanks, generally did not possess methanogens, as assayed by PCR specific for methanogen 16S rRNA genes, nor did artificial catchments ( 100 ml volume), in place 6-12 months prior to sample collection. Methanogens were not detected in soil (n = 20), except in one case, in which the dominant ribotype was different from nearby bromeliads. Recovery of methyl coenzyme M reductase genes supported the occurrence of hydrogenotrophic and aceticlastic methanogens within bromeliad tanks, as well as the trend, via QPCR analysis of mcrA, of increased methanogenic capacity with increased plant height. Methane production rates of up to 300 nmol CH4 ml tank water -1 day-1 were measured in microcosm experiments. These results suggest that bromeliad-associated archaeal communities may play an important role in the cycling of carbon in neotropical forests.